Planning towards retirement - San Juan, Sofrionio P.
We look and eventually retire. If we want to enjoy that period in our life, planning for it starts as we commence the practice of our profession. Preparing for it encompasses the whole gamut of a person's physical, emotional and materials needs. Oftentimes, the stress in on financial security. However, its importance could yield to a deeper emotional and intellectual fulfillment. And the secret is to ease into it instead of abruptly stopping our professional or social commitments.
Keywords: Investments; Inflation; Inventory of assets; Spiritual life; Emotional cost; Community service; Lifestyle